Relay intercropped soybean promotes nodules development and nitrogen fixation by root exudates deposition - Lin, Ping; Wang, Jin; Chen, Ping; Fu, Zhidan; Luo, Kai; Li, Yiling; Pu, Tian; Wang, Xiaochun; Yong, Taiwen; Yang, Wenyu (Frontiers in Plant Science, 2024)
BackgroundLegumes, in the initial event of symbiosis, secrete flavonoids into the rhizosphere to attract rhizobia. This study was conducted to investigate the relationship between crop root exudates and soybean nodule development under intercropping patterns.MethodA two years field experiments was carried out and combined with pot experiments to quantify the effects of planting mode, i.e., relay intercropping and monocropping, and genotypes, i.e., supernodulating NTS1007(NTS), Nandou-12(ND) and Guixia-3(GX) on root exudates, rhizobium community structure, nodule development and nitrogen fixation ability.ResultThe result demonstrated that, maize–soybean relay strip intercropping not only promoted daidzein and genistein exudates of soybean root to soil but also reshaped the community structure and diversity of nodule endophytic rhizobia. Compared with monocropping, the nodule number significantly decreased in relay strip intercropping soybean, and NTS achieved 97% at soybean five trifoliolate stage. At soybean full bloom stage, despite the nodulation capacity of relay strip intercropping soybean was unrestored, the nodule number, nodule dry weight, nodule diameter and root dry weight were the highest in ND under relay strip intercropping. Compared with monocropping, the nodule average diameters of ND and GX in relay strip intercropping significantly increased 26.30% and 21.11%, respectively, the single nodule nitrogenase activity and nifH gene was increased up to the higher level of 3.16-fold and 1.96-fold, 70.8% and 107.6%, respectively. Combined with pot experiments, the nodule number of ND and NTS in maize root maize root exudates (RE) treatment increased with growth period, the GX reached its maximum at full bloom stage. And the nodule diameter of ND under RE treatment showed the best response. At R2 stage, compared with distilled water (DW) treatment, the nodule average diameter of ND and GX in RE treatment was significantly higher, and the GmEXPB2 gene was significantly up-regulated 3.99-fold and 1.02-fold, respectively.ConclusionIn brief, the maize–soybean relay strip intercropping enhanced the soybean root exudates nodulation signaling molecules, meanwhile, maize root exudates caused increased nodule diameter, and enhanced nodule nitrogen fixation, but had little effect on supernodulation varieties.